Multilevel Analysis of Project and Team competencies for Cost and Time Project Management Success in Construction Projects - Iqbal, Naveed; Awan, Maira; Waseem, Muhammad (UW Journal of Management Sciences, 2023)
Purpose: Excessive costs and unexpected schedule setbacks are pervasive challenges encountered by countries globally. Insufficiently skilled teams elevate the risk of project delays. The behavioral dimensions of a project, encompassing intellectual, emotional, and contextual competencies at both individual and project levels, are often overlooked but play a vital role in the success of project management. Design and Methodology: The study’s sample data was gathered from project managers through a survey based on questionnaires. Only completed projects from the construction industry of Pakistan are selected for this study The responses collected serve as the foundation for conducting statistical analysis using multiple regression techniques. Findings: The study reveals that the project manager’s contextual and technical competency, coupled with the intellectual and emotional competence of the team, positively influences the CTPM success of construction projects. Conversely, knowledge and value diversity have been identified as factors with a negative impact on CTPMS. Additionally, Greater project size heightens the risk of delays and cost overruns, attributed to increased time spent on communication and collaboration within larger teams, posing challenges to budget adherence. Implications: This research addresses the gap in existing literature by conducting a three-level analysis—project-level, project manager-level, and project team-level—to examine their collective impact on project management success, with a specific focus on cost and time considerations. The findings hold significant implications for project managers shedding light on the dynamics influencing the project management success. The manager can make better decisions to execute projects efficiently and cost effectively. Keywords: Multi-level factors, Project cost and time management success, Construction industry, Project Manager, Project Team